Institutionalizing Digital Trade Governance in Africa: AfCFTA, PAPSS, and the Politics of Regional Infrastructure Gaps - Habib Budiman; Arya Luthfi Permadi; Wahyu Wulandari (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2026)
This article analyzes how the African Continental Free Trade Area (AfCFTA) and the Pan-African Payment and Settlement System (PAPSS) institutionalize digital trade governance in Africa amid persistent infrastructure gaps, regulatory fragmentation, and asymmetric dependence on external payment and data infrastructures. Using a qualitative descriptive-analytical design, this study examines official policy documents, multilateral reports, and peer-reviewed scholarship on digital trade, regional integration, data governance, and international political economy. The analysis applies neoliberal institutionalism while engaging critical debates on digital sovereignty and digital colonialism. The findings show that AfCFTA has moved beyond a conventional trade liberalization project by becoming a continental rule-making forum for digital trade, data flows, consumer protection, cybersecurity, and electronic transactions. PAPSS complements this legal architecture by reducing cross-border payment frictions, lowering dependence on third-party currencies, and retaining more financial data within African institutional circuits. However, the study also finds that institutional effectiveness remains constrained by national sovereignty resistance, fiscal protectionism, uneven cyber-regulatory capacity, weak enforcement mechanisms, and overlapping regional economic communities. The article argues that Africa’s pursuit of inclusive digital sovereignty depends not only on adopting continental rules, but also on aligning domestic laws, financing hard infrastructure, strengthening supranational coordination, and designing fair adjustment mechanisms for weaker member states. The study contributes to debates on regionalism by showing that digital trade integration requires legal harmonization, operational payment infrastructure, and credible compliance capacity at the same time.